Deposição atmosférica total em uma região agrícola do Sul de Minas Gerais: avaliação da composição química e contribuição de fontes - Pereira, Jaqueline Natiele (2022)
Atmospheric deposition is a key mechanism for the chemical compounds cycling between environmental ecosystems, since provides useful information about the atmosphere chemical composition, reaction pathways and environmental impacts, as well as information that feeds receptor models to identify the sources apportionment. Given this perspective, this study evaluated the chemical composition of atmospheric deposition in order to quantify its acidity, its fluxes and ecological impacts and natural and anthropogenic sources contribution, in the Lavras city, Southern Region of Minas Gerais. Bulk atmospheric deposition collector was used, which was installed on the Universidade Federal de Lavras campus (UFLA) and was exposed to open field for weekly collections of rainwater (wet deposition) and particulate matter (dry deposition). A dataset of 59 samples was collected between March 2018 and October 2019, in which we performed pH, electrical conductivity and ion chromatography analyzes to quantify Ca2+, Na+, NH4+, Mg2+, K+, Cl−, NO3− e SO42−. For better understanding, the results obtained in this study were discussed in three articles. The first one, entitled Atmospheric deposition chemistry in a Brazilian rural area: alkaline species behavior and agricultural inputs, showed that most of atmospheric deposition samples were alkaline, Ca2+ was the dominant species and the main neutralizing agent of acidic species. In the second article, we applied the EPA PMF 5.0 model to investigate the sources contribution to the atmospheric deposition species and we found three sources: neutralization atmospheric processes, crustal processes and fires, and fertilizers production and application. The third article, entitled Nitrogen Atmospheric Deposition Driven by Seasonal Processes in a Brazilian Region with Agricultural Background, had the collaboration of researchers from the Programa de Pós-Graduação em Recursos Hídricos at UFLA, who provided data on wet deposition of total kjeldahl nitrogen, allowing quantification of total dissolved nitrogen (TDN), dissolved organic and inorganic nitrogen fluxes (DON and DIN, respectively). This article revealed a dominant DON flux and that DIN flux had the potential to cause acidification and eutrophication in environmental ecosystems. In general, the results presented in the three articles provide critical information for the policies formulation aimed at reducing pollutant emissions in the region of Lavras-MG.